Penerapan Cooler Box Bertenaga Panel Surya untuk Meningkatkan Kualitas Hasil Tangkapan Nelayan di Daerah Kepulauan - Wibowo, Sadiq Ardo; Handayani, Vitri Aprilla; Hernando, Luki; Devikaduri, Laras; Tuto Bakang, Clarita; Eka Candra, Joni (Jurnal SOLMA, 2025)
Background: Limited fish storage facilities are a major factor contributing to the decline in fish quality among fishermen in island areas, which ultimately reduces market value. This community service activity aimed to implement a solar-powered cooler box as an efficient and environmentally friendly storage solution for fishermen in remote coastal regions. Method: The method included a needs assessment, design and installation of a 40-liter cooling system with a 100 WP solar panel, and training on operation and maintenance for fishermen in the Belakang Padang Islands. Results: The results showed that the storage temperature could be maintained between 2–4°C for 8–10 hours daily without relying on conventional electricity. The use of this equipment reduced the spoilage rate of fish from an average of 28% to 10%, and increased selling prices by an average of 18%. Conclusion: This program demonstrates that renewable energy technologies can contribute to improving the quality of fish catches and the economic well-being of fishermen in a sustainable manner.